Pengembangan Modul Edukasi Kanker Payudara Berbasis Android pada Wanita Subur - Debbie Nomiko; Abbasiah Abbasiah; Bettywaty Elliezer; Muthia Muthmainah (Journal of Telenursing (JOTING), 2022)
This study aims to design the development of a breast cancer educational application module for women of childbearing age. The research and development method involved 45 women of childbearing age selected by purposive sampling at the Pakuan Baru Health Center, Jambi City. The data collected is the acceptance of respondents regarding the application, characteristics of respondents, understanding of breast cancer and awareness. The instruments used in this study were questionnaires for understanding respondents and smartphones. Data analysis was performed using the dependent t-test technique. The results showed a significant difference in the mean pre-test results related to knowledge compared to the post-test with a p-value of 0.000. In conclusion, the breast cancer education application (EDUKARA) can increase respondents' understanding of breast cancer and how to prevent it through breast self-examination (BSE). Keywords: Application, Education, Breast Cancer, Breast Self Examination